2005
DOI: 10.1103/physrevd.71.067301
|View full text |Cite
|
Sign up to set email alerts
|

Loitering universe models in light of the CMB

Abstract: Spatially flat loitering universe models have recently been shown to arise in the context of brane world scenarios. Such models allow more time for structure formation to take place at high redshifts, easing, e.g., the tension between the observed and predicted evolution of the quasar population with redshift. While having the desirable effect of boosting the growth of structures, we show that in such models the position of the first peak in the power spectrum of the cosmic microwave background anisotropies se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
(8 reference statements)
1
20
0
Order By: Relevance
“…The use of the WMAP constraint on R is a gross simplification of the CMB data (see Elgaroy & Multamaki 2007) since it is model‐dependent. Tensor modes, for example, may affect the reported constraint.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the WMAP constraint on R is a gross simplification of the CMB data (see Elgaroy & Multamaki 2007) since it is model‐dependent. Tensor modes, for example, may affect the reported constraint.…”
Section: Resultsmentioning
confidence: 99%
“…A flat universe, k = 0, is assumed in all the expressions below. Hubble parameter: H[z(y)] = H 0 1 + (q 0 + 1)y + y 2 j 0 2 − q 2 0 2 + q 0 + 1 + 5 Of course, CMB observables can be used within a given gravitational dynamics to fix the free variables of a cosmological model [54] and hence calculate the corresponding cosmographic parameters to be confronted with those determined purely on the base of standard candles and rulers, as we also showed as application to the evaluation of cosmographic parameters in several cosmological models.…”
Section: Appendix: Series Expansionsmentioning
confidence: 99%
“…where z * is the redshift of decoupling, D A (z) is the proper angular diameter distance to redshift z, and r s (z) is the comoving sound horizon at z. It was shown that these two quantities contain almost all of the information required to constrain dark energy with CMB [26][27][28]. For future CMB data, we used the Planck characteristics for parameters and their errors [29].…”
Section: Cmb and Bao Datamentioning
confidence: 99%